Modelo de expansión de un sistema de transmisión basado en linealización de flujos óptimos de potencia AC. - Escudero Delgado, Pablo Vinicio (2018)
In the present work a model for the expansion of a transmission system is analyzed, by means of which an optimal flow of AC power (OPF-AC) is developed where an accurate analysis of the flow circulating through said network is carried out. While the expansion through OPF-AC is a problem of mixed non-linear programming (MINLP) for transmission expansion planning (TEP) and by the complexity of solving an OPF-AC for a robust problem and that depends on the size of the electrical system of power to analyze (SEP). We proceed in said document to transform these equations that make up an OPF-AC into a system of linear constraints using Taylor series, for which a precise and applicable model will be acquired in order to guarantee the minimization of both operating costs in generation and investment costs, having minimal losses and thus having a reliable model to the 39-bar system of the IEEE.